PI3K signaling in arterial diseases: Non redundant functions of the PI3K isoforms. (September 2015) - Lupieri, Adrien; Smirnova, Natalia; Malet, Nicole; Gayral, Stéphanie; Laffargue, Muriel
Abstract: Cardiovascular diseases are the most common cause of death around the world. This includes atherosclerosis and the adverse effects of its treatment, such as restenosis and thrombotic complications. The development of these arterial pathologies requires a series of highly-intertwined interactions between immune and arterial cells, leading to specific inflammatory and fibroproliferative cellular responses. In the last few years, the study of phosphoinositide 3-kinase (PI3K) functions has become an attractive area of investigation in the field of arterial diseases, especially since inhibitors of specific PI3K isoforms have been developed. The PI3K family includes 8 members divided into classes I, II or III depending on their substrate specificity. Although some of the different isoforms are responsible for the production of the same 3-phosphoinositides, they each have specific, non-redundant functions as a result of differences in expression levels in different cell types, activation mechanisms and specific subcellular locations. This review will focus on the functions of the different PI3K isoforms that are suspected as having protective or deleterious effects in both the various immune cells and types of cell found in the arterial wall. It will also discuss our current understanding in the context of which PI3K isoform(s) should be targeted for future therapeutic interventions to prevent or treat arterial diseases.